Lymphoepithelial cyst in the palatoglossus arch - Evanice Maria Marçal Vieira; Vinícius Canavarros Palma; Tereza Aparecida Delle Vedove Semenoff; Andreza Maria Fábio Aranha; Flares Baratto-Filho; Álvaro Henrique Borges (Editorial Ciencias Médicas, 2012)
The objective of this study was to describe a case of a lymphoepithelial cyst in the palatoglossus arch. A 16-years-old black man said that he was observed a lesion in his mouth. On the physical exam, a pedicled, consistent, smooth surface 1.5 x 1 cm lesion, similar in color to the adjacent mucosa, was found. The lesion was surgically removed and the microscopic exam showed mucosal fragments with pedicled lesion; the cystic cavity sometimes lined with pseudostratified cylindrical epithelium and others with stratified squamous flat interface of the epithelium. Around the cyst, a well-delimited mass of lymphoid tissue, presenting lymphoid follicles, was also seen. Lymphoepithelial cyst has clinical characteristics similar to those of others lesions that occur in the oral cavity. The diagnosis should be based on conservative biopsy, with total removal of lesion.